A new multi-objective profit-driven micro-CHP planning model under participation in thermal and electrical markets. (5th January 2023) - Hamzehkolaei, Fatemeh Teymoori; Amjady, Nima; Ghamsari-Yazdel, Mohammad; Jazaeri, Mostafa
Highlights: A new profit-based residential µCHP planning model is presented. Participation of µCHP system in electrical and thermal markets is modeled. The proposed µCHP planning model has multi-objective structure. A new multi-objective solution method is proposed. The validity of the contributions is illustrated on a real-world case study. Abstract: Recently, residential micro-combined heat and power (µCHP) systems have been increasingly used worldwide and simultaneously participated in thermal and electrical markets. To enhance practicality of µCHP system planning (MSP), this research proposes a new multi-objective optimization model for MSP considering investment costs and participation profits in thermal and electrical markets. A multi-objective optimization problem includes more than one objective and usually these objectives are competing which means that there is no single optimal solution that simultaneously optimizes all of them. Maximizing the participation profits along with minimizing investment costs can more effectively persuade investors to invest on MSP. Additionally, exergy efficiency and thermal discomfort level are considered in the proposed multi-objective model. Moreover, an improved lexicographic weighted Tchebycheff (ILWT) approach is developed for solving the proposed multi-objective MSP problem, which generates effective Pareto optimal solutions with a low computation burden. The proposed MSP model and ILWT solution approach are tested on a real-world µCHP system. It is shown that the proposed MSP model achieves a significant total cost reduction by the amount of 24.5% compared with conventional MSP model. Also, the proposed ILWT, compared with its nearest competitor, obtains about 3% higher preference with more than 39% lower computation time.